2023
DOI: 10.3389/fnut.2023.1011958
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of the evidence-diagnosis link predicts nutrition diagnosis resolution in the Academy of Nutrition and Dietetics' diabetes mellitus registry study: A secondary analysis of Nutrition Care Process outcomes

Abstract: ObjectivesTo describe nutrition care documentation patterns and investigate predictors of nutrition diagnosis resolution.MethodsThis is a secondary data analysis of a 2-year pragmatic, quasi-experimental study conducted in outpatient clinics where nutrition care was provided to adults with diabetes Type 1 or 2 from May 2017 to June 2019 (n = 564 patients). The main outcome measures were frequency of standardized Nutrition Care Process (NCP) terms, NCP links, nutrition diagnosis resolution and predictors of nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 18 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…To assess critical thinking in EPRs, NCP audit tools should be performed. 8,20,21 In our study, Diet-NCP-Audit items evaluating nutrition intervention (step 3) and nutrition monitoring and evaluation (step 4) received higher scores than steps 1 and 2, even if they were not NCP steps covered by training at the HFR. This finding is consistent with some old and recent papers in which dietitians perceived steps 3 and 4 as less complicated than nutrition diagnosis.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…To assess critical thinking in EPRs, NCP audit tools should be performed. 8,20,21 In our study, Diet-NCP-Audit items evaluating nutrition intervention (step 3) and nutrition monitoring and evaluation (step 4) received higher scores than steps 1 and 2, even if they were not NCP steps covered by training at the HFR. This finding is consistent with some old and recent papers in which dietitians perceived steps 3 and 4 as less complicated than nutrition diagnosis.…”
Section: Discussionmentioning
confidence: 52%
“…21 These authors recently showed that the NCP evidence-diagnosis link was the most likely link to increase the odds of diagnosis resolution. 21 And Lewis and colleagues found that this link was the second most likely to do it. 20 Therefore, dietitians should monitor signs and symptoms coming from the assessment part to verify the effectiveness of their interventions on nutrition problems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations